The Development of CEFR-Based Nahwu and Shorof Learning Evaluation in Madrasah Aliyah in Cirebon - Muhammad Yusril Muna; Zainal Arifin Ahmad; Irfan Hania; Faizmailiatus Sofa; Sri Utami; Putri Nurinadia (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2022)
This study aims to determine the implementation and development of CEFR-based nahwu and shorof learning evaluations at MA An-Nur Jagasatru Cirebon. The research methodology used is the research and development method. In the development of this research, we used the Rowntree model, which was consisted of three stages, namely the planning stage, the development stage, and the evaluation stage. The trial phase began with the validation of material experts and linguists. Then, after being revised, the product was tested on class X students, namely 8 students for testing prototype 1 and 21 students for testing prototype 2. The results showed that the average score of material experts was 85%, which meant the product was considered very good, and linguists 88%, which meant the product was considered very good. Then at the testing stage of prototype 1, an average score of 64.37, which meant the product was considered quite good, and at the testing stage of prototype 2, an average score of 74.71, which meant it was considered very good. Based on interviews with teachers, they obtained very good results. Based on the results of the study, it can be concluded that the evaluation of nahwu and shorof learning based on CEFR is feasible and effective as an evaluation tool in nahwu and shorof learning, especially in MA An-Nur Jagasatru Cirebon.